Perlindungan Hukum kepada Perusahaan Asuransi terhadap Tindakan Fraud yang dilakukan oleh Nasabah di Indonesia - Anandri Farrasadre Muhammad; Ery Agus Priyono (Universitas Batanghari Jambi, 2023)
Within the insurance often found crime, one of which is an act of fraud committed by the customers. Acts of fraud committed by the customers often resulting in losses to the insurance company. Therefore, it is important to provide legal protection for insurance companies so that fraud by the customers can be prevented. To answer the above problems, the method used by researchers is normative juridical by examining Indonesia's positive law that provides legal protection to insurance companies. An important finding in this studies is to find out how the reality facts about this problem and how legal protection is preventive and repressive